2019
DOI: 10.1177/2325958219888463
|View full text |Cite
|
Sign up to set email alerts
|

A Chart Review Study of Sexually Transmitted Infections Among Persons Living with HIV Attending an STI Clinic in Trinidad

Abstract: A chart review study of the sexually transmitted infection (STI) prevalence among persons living with HIV (PLHIV) was conducted among STI clinic attendees in Trinidad between January 2012 and December 2012. Data were abstracted from client records to obtain the clinical and the laboratory diagnoses of STIs. Descriptive and bivariate analyses were conducted, and factors significantly associated with the presence of a STI were assessed using multiple logistic regression. During this period, 385 PLHIV were seen; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The prevalence of syphilis in MSM living with HIV in this study was found to be higher than PLHIV (13.2%–21.0%) attending the STI clinic in Trinidad 17,18 and among heterosexual males (17.3%) attending a STI Clinic in Jiangsu Province in China. 22 Our study findings of high levels of syphilis//HIV coinfection in MSM are consistent with findings in the literature in other regions and settings.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The prevalence of syphilis in MSM living with HIV in this study was found to be higher than PLHIV (13.2%–21.0%) attending the STI clinic in Trinidad 17,18 and among heterosexual males (17.3%) attending a STI Clinic in Jiangsu Province in China. 22 Our study findings of high levels of syphilis//HIV coinfection in MSM are consistent with findings in the literature in other regions and settings.…”
Section: Discussioncontrasting
confidence: 44%
“…In 2013, Mungrue et al 16 studied 64 cases of confirmed syphilis at the sexually transmitted infection (STI) clinic in Trinidad and found that 36.6% of those cases were diagnosed in persons who self-identified as MSM. Two cross-sectional studies were conducted to determine the prevalence of STIs among PLHIV attending the STI clinic in Trinidad in 2012 17 and 2014, 18 respectively, and the prevalence of syphilis among PLHIV increased from 13.2% in 2012 17 to 21.0% in 2014. 18 In the 2014 study, 18 STIs were more common in MSM, and the most common STI diagnosed in these patients was syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…Testing for HIV was done using Alere Determine V R HIV-1/2 Ab rapid test (Alere Inc., Waltham, MA, USA) and the Uni-Gold A chart review study which examined the charts of all PLHIV who attended the QPCC&C in 2012 showed that 385 PLHIV attended the STI clinic that year. 19 Hence for a population of 385 clients at the 95% confidence level with a confidence interval of 5, the sample size would be 193. Patients less than 18 years of age and HIV-seronegative individuals were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…A chart review study which examined the charts of all PLHIV who attended the QPCC&C in 2012 showed that 385 PLHIV attended the STI clinic that year. 19…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of STIs among PLHIV attending the STI Clinic in Trinidad was found to be 35.1% in 2012 [ 9 ] and 37.1% in 2014 [ 10 ] in two cross-sectional studies and STIs were found to be more common in MSM in whom syphilis was the most commonly diagnosed STI [ 10 ]. In these studies, the prevalence of syphilis increased from 13.2% in 2012 (9) to 21.0% in 2014 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%